Given f(x)=3x^2-7x+2, determine f(x+h)-f(x)?

1 Answer
Feb 12, 2018

f(x+h)f(x)=6xh+3h27h

Explanation:

f(x+h)f(x)=3(x+h)27(x+h)+2(3x27x+2)

f(x+h)f(x)=3(x2+2xh+h2)7x7h+23x2+7x2

f(x+h)f(x)=3x2+6xh+3h2+23x2+7x2

Simplifying...

f(x+h)f(x)=6xh+3h27h

I will say that you would normally see this question asked:

Find f(x+h)f(x)(x+h)x

This is the formula associated with finding derivatives in calculus. But if you just need the top (numerator), it is f(x+h)f(x)=6xh+3h27h
Just make sure that you are answering the right question!